The importance of intercoder agreement for content analysis - Peña y Lillo, Macarena (Universidad de Chile. Instituto de la Comunicación e Imagen, 2012)
Content analysis is a widely utilized technique by researchers on mass media. Generally, researchers in quantitative content analysis rely on several coders to enter the data. A key question they face is whether it is possible to assure that the coders’ decisions are consistent across the analysis. It is expected for different people to have different interpretations of the texts, which threatens the reliability of the obtained results and the study’s conclusions. In order to avoid this threat, researchers must evaluate and report intercoder agreement. In this essay, arguments for this practice are presented and a reflection about its use on an empirical case study is offered